Implementation of Problem Based Learning with Gamification Approach - Handikaningtyas, Tristania; Kenya, Ponasari Baron Mutiara; Ramadhan, Aditya; Fajarianto, Otto; Nurlia, Titim (IJESS International Journal of Education and Social Science, 2024)
The 21st century learning presents significant challenges in the learning process. In this context, critical thinking, creativity, collaboration and communication skills are important skills that students must master. This study aims to explore the implementation of Problem-Based Learning (PBL) integrated with a gamification approach as a solution to improve 21st century skills in students. This research uses the systematic literature review (SLR) method with the inclusion criteria of review articles published within the last 5 years and covers the research area of gamification in Problem-Based Learning (PBL) to improve 21st century skills. Problem-Based Learning (PBL) provides meaningful learning experiences through learning activities that are relevant to the real world and can encourage students to actively participate in the learning process. However, there are challenges in maintaining the consistency of students' motivation and active involvement in learning. The implementation of PBL with a gamification approach is proven to show a significant increase in students' critical, creative and collaborative skills. However, in this context, educators' skills in designing learning by incorporating gamification elements are important factors in determining the success of gamification. The results of this study are expected to contribute positively to the development of effective and joyful learning models. It is also expected that the results of the research can provide recommendations for the creation of an interactive learning environment and support the achievement of mastery of 21st century skills in students.